2014
DOI: 10.1002/2014jc010055
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of suspended particulate matter in turbid oyster‐farming ecosystems

Abstract: High resolution satellite data of the Medium Resolution Imaging Spectrometer in full resolution mode (MERIS FR, pixel size is 300 m) were used to study the impact of suspended particulate matter (SPM) on oyster‐farming sites in a macrotidal bay of the French Atlantic coast where SPM concentration can exceed 100 g m−3. Because MERIS standard SPM concentration retrieval saturates at about 50 g m−3, we developed an alternative method for turbid nearshore waters. The method consists in the combination of the Semi‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…Due to tidal resuspension, SPM concentration seldom decreases below 50 g m −3 and regularly exceeds 500 g m −3 . As a too high SPM concentration impacts oyster clearance rate and other physiological functions , oysters grown in this farming site are negatively impacted by high SPM concentration (Gernez et al, 2014). Daily mean chl a concentration was reported to vary between 4 and 14 mg m −3 (Dutertre et al, 2009), and monthly means between 5 and 30 mg m −3 were previously reported at the study site .…”
Section: Study Sitementioning
confidence: 64%
See 3 more Smart Citations
“…Due to tidal resuspension, SPM concentration seldom decreases below 50 g m −3 and regularly exceeds 500 g m −3 . As a too high SPM concentration impacts oyster clearance rate and other physiological functions , oysters grown in this farming site are negatively impacted by high SPM concentration (Gernez et al, 2014). Daily mean chl a concentration was reported to vary between 4 and 14 mg m −3 (Dutertre et al, 2009), and monthly means between 5 and 30 mg m −3 were previously reported at the study site .…”
Section: Study Sitementioning
confidence: 64%
“…Oyster clearance rate was computed from SPM concentration as in using a non-linear function response (see also Figure 3 in Gernez et al, 2014). Briefly, oyster clearance rate is constant and equal to 4.8 L h −1 when SPM concentration is lower than 60 g m −3 .…”
Section: Simulating Oyster Physiology From Spacementioning
confidence: 99%
See 2 more Smart Citations
“…R rs signal appears to be far from zero in the near-infrared wavelengths for the most turbid waters (e.g. Doxaran et al, 2003;Gernez et al, 2014). In such turbid…”
Section: Figurementioning
confidence: 99%